New Oxford textbook of psychiatry - Andreasen, Nancy C.; Lopez-Ibor , Juan J. Jr; Geddes, John R. (Oxford University Press, 2012)
This two-volume set is the definitive source for all practising psychiatrists. It covers all areas of general psychiatry in depth, and includes sections on each of the subspecialties including child psychiatry and forensic psychiatry.